Aluminum thin film enhanced IR nanosecond laser-induced frontside etching of transparent materials. (January 2017) - Nieto, Daniel; Cambronero, Ferran; Flores-Arias, María Teresa; Farid, Nazar; O'Connor, Gerard M.
Abstract: Laser processing of glass is of significant commercial interest for microfabrication of precision optical engineering devices. In this work, a laser ablation enhancement mechanism for microstructuring of glass materials is presented. The method consists of depositing a thin film of aluminum on the front surface of the glass material to be etched. The laser beam modifies the glass material by being incident on this front-side. The influence of ablation fluence in the nanosecond regime, in combination with the deposition of the aluminum layer of various thicknesses, is investigated by determining the ablation threshold for different glass materials including soda-lime, borosilicate, fused silica and sapphire. Experiments are performed using single laser pulse per shot in an air environment. The best enhancement in terms of threshold fluence reduction is obtained for a 16 nm thick aluminum layer where a reduction of two orders of magnitude in the ablation threshold fluence is observed for all the glass samples investigated in this work. Highlights: New laser-induced frontside etching method of transparent materials is presented. A thin film metal coating is used to couple the light at surfaces of transparent materials. It was obtained a reduction of two orders of magnitude in the ablation threshold of different glass materials. It was obtained a reduction of morphology features (depth and diameter) of microstructures fabricated in glass.